The Imperfect Intermediation of Money‐Like Assets - STEIN, JEREMY C.; WALLEN, JONATHAN (Journal of Finance, 2025)
ABSTRACT We study supply‐and‐demand effects in the U.S. Treasury bill market by comparing the returns on T‐bills to the policy rate on the Federal Reserve's reverse repurchase (RRP) facility. We develop and test a simple model where the RRP‐bill spread is policed both by heterogeneously elastic money funds and by corporate treasurers who derive collateral benefits from holding T‐bills. In response to shifts in T‐bill supply, money funds act as front‐line arbitrageurs. However, when T‐bills become extremely scarce, less elastic corporate treasurers become the marginal investors and supply shifts have a larger effect on T‐bill rates.